2019
DOI: 10.1007/s10995-019-02773-w
|View full text |Cite
|
Sign up to set email alerts
|

A Novel 4D Ultrasound Parenting Intervention for Substance Using Pregnant Women in Finland: Participation in Obstetric Care, Fetal Drug Exposure, and Perinatal Outcomes in a Randomized Controlled Trial

Abstract: Objectives The aim of the study was to explore the effect of a new prenatal intervention on participation in obstetric care, fetal drug exposure, and perinatal outcomes among substance using pregnant women in Finland. Methods The participants were 90 women referred to a hospital obstetric outpatient clinic due to current or recent substance use. The intervention group (n = 46) was offered three interactive ultrasounds at 24, 30 and 34 gestational weeks and a pregnancy diary accompanied by three prenatal infant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…Finally, it is worth noting that a great number of studies addressing substance use with RCTs also consider other aspects of the well-being of pregnant women, such as family cohabitation, employment integration, and accessibility to healthcare resources. However, they do not report measures of psychopathology; hence, it cannot be considered that they address dual pathology [38,47,52,57,58,67,68,76,79,85,88,90].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, it is worth noting that a great number of studies addressing substance use with RCTs also consider other aspects of the well-being of pregnant women, such as family cohabitation, employment integration, and accessibility to healthcare resources. However, they do not report measures of psychopathology; hence, it cannot be considered that they address dual pathology [38,47,52,57,58,67,68,76,79,85,88,90].…”
Section: Resultsmentioning
confidence: 99%
“…Jussila et al conducted a novel, randomized controlled trial among pregnant women attending an obstetric outpatient clinic in Finland. 43 Ninety women were referred to the clinic because of current or recent substance use—defined as self-reported or documented illicit substance use, abuse of prescription medication or alcohol within the past 3 years or during a previous pregnancy, and/or a score of 3 or higher on the Tolerance-Worry-Eye-Opener-Annoy-Cut-Down (TWEAK) alcohol screening tool. They were randomized either to a control group ( n = 44) receiving treatment as usual or to an intervention group ( n = 46) that included interactive use of 4D ultrasound visualization of the fetus at 24, 30, and 34 weeks and a pregnancy diary.…”
Section: Resultsmentioning
confidence: 99%
“…Pulliainen et al [72] performed a qualitative pilot study with pregnant women at high risk for preterm birth and showed that interactive 3D ultrasounds shown at the request of the pregnant women increased MFA. A randomized controlled trial of a 4D ultrasound intervention among pregnant women with substance use demonstrated a higher retention rate, as well as enhanced MFA, in the intervention group compared to the control group [73].…”
Section: Discussionmentioning
confidence: 97%